CHARACTER BUILDING: ARE EFL TEACHERS READY? (VOICES FROM LANGUAGE CLASSROOMS) - Wiyati , Retno (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2019)
Character building education in classroom contexts is nowadays gaining a lot more attention than in the past as a way to provide solution to the social misbehavior that students often conduct outside classroom and even school levels. This is in line with the new curriculum of 2013 in which “Pendidikan nasional berfungsi mengembangkan kemampuan dan membentuk watak serta peradaban bangsa yang bermartabat....peserta didik agar menjadi manusia yang beriman dan bertakwa kepada Tuhan yang Maha Esa, berakhlak mulia,sehat, berilmu, cakap, kreatif, mandiri, dan mejadi warga negara yang demokratis serta bertanggung jawab (Suherdi, 2013). This indicates that character building education is very important in producing students who have a strong religious character as well as a good attitude to make them not only succeed academically in school but also in their social life. This study is thus aimed at finding out the aspects of characters that teachers and students need to possess, the teachers’ role in promoting character education in the classrooms, and the importance of character education to enhance students’ learning activities. This study involves several teachers and students of different classes from some English learning institutions. The preliminary study revealed that teachers do not have a significant role in emphasizing character building in the classrooms and that most students are not fully aware of the importance of character education in enhancing their learning.